Development of Processing Technique for the Production of Chilli (Capsicum Annuum Variety Kulai) Puree - Sari, Ermina (2007)
Chilli puree is a product in semi-solid form having quality close to the fresh ones and is convenient to use. At present, the quality of chilli puree in the market is not acceptable to the food manufacturers as a raw material for making other products derived from chilli as it contains high amount of preservatives and has unattractive dark colour. Therefore, development of an appropriate processing technique for production of chilli puree having a quality acceptable to the users is of prime importance. Response surface methodology (RSM) was used to determine the optimum conditions for drying chilli. Fresh chilli was dried using two different techniques; cabinet and vacuum oven dryer. Changes in the Hunter colour parameters (L, a, b) of chilli during drying were investigated. Sensory evaluation was used to determine the quality of dried chilli in terms of colour, texture, aroma and overall acceptability. It found that changes in colour during drying of chilli by cabinet oven drying were apparent. On the other hand, an increase in the temperature of vacuum oven dryer did not give significant effect on the colour of dried chilli produced. The optimum conditions for the cabinet oven drying of chilli were found to be at 50oC for 5 days, while that of vacuum oven drying was at 80oC for 7 hours. Dried chillies (Capsicum annuum variety Kulai) were reconstituted using two different soaking techniques (cold water and boiled water soakings), crushing and stone-grinding into fine puree and pasteurized with and without citric and/or acetic acids. The quality attributes of chilli puree were evaluated in terms of pH, moisture, Hunter surface colour (L, a, b and hue angle and chroma), extractable colour (ASTA units) and capsaicinoid content. Results showed that different soaking techniques had a pronounced effect on the pH, moisture content, Hunter surface colour, extractable colour, hue angle and chroma and of the puree. However, chilli puree prepared by boiled-water soaking had lower capsaicin and di-hydro capsaicin concentrations compared to cold water soaking. Pasteurization at different pHs did not seem to give an effect on the Hunter surface colour (L, a, and b), ASTA unit and pungency of the purees produced. Overall, the combined treatments of boiled water soaking and pasteurized in the presence of acid(s) conferred purees of similar quality attributes. The colour degradation kinetics of chilli puree prepared from dried chilli (Capsicum annuum variety Kulai) was evaluated using a fraction conversion technique during thermal treatment at 60, 70, 80 and 90oC (up to 30 min) and storage of chilli puree at 5, 28 and 45oC (up to 10 weeks). Chilli puree was subjected to heat treatment at different temperatures in a well-stirred water bath. Test samples were removed from the water bath at selected time intervals (0-30 min after come-up), cooled immediately and analyzed for colour using Hunterlab colorimeter. Chilli puree colour was expressed in terms of tristimulus colour value a and combination (L x a x b). First order reaction kinetics adequately described the change in colour values during both thermal treatment and storage of puree. The quality of chilli puree stored at three different storage conditions during 10 weeks of storage were evaluated in terms of pH, water activity, Hunter colour (L, a, b and hue angle and chroma), extractable colour (ASTA units), capsaicinoid content, volatile compounds and microbiological quality. Different storage conditions used had significant effects on the hunter surface colour, extractable colour, hue angle and chroma, volatile compounds and microbiological quality of the final puree product. Capsaicinoids, pH and water activity values were retained during storage. Data obtained in this study showed that a combination of low temperature storage, pH and heat treatment synergistically enhanced the quality of chili puree and prolonged its shelf life.